Resolution of Value Conflicts in Multicultural Counselling - Merali, Noorfarah (Canadian Journal of Counselling and Psychotherapy, 2007)
Reports of value conflicts between counsellors from the dominant group and culturally different clients have served as the impetus for matching counsellors and clients based on cultural background, as well as for the development of the Theory of Multicultural Counselling and Therapy (MCT). The assumption of cultural homogeneity that underlies the strategy of counsellor-client match is challenged based on the processes of free will and acculturation. Incongruities in the theory and practice of MCT are highlighted with respect to cultural bias in language and intervention choice. An innovative, disclosure-based alternative to resolving counsellor-client value conflicts is presented. The application of the approach is illustrated through a multicultural case in which the principles of integrity in relationships and responsible caring in the Canadian Psychological Association's ethical guidelines diverge.